- Teachers’ Strategies to Enhance Classroom Interaction by Using Linguistic Modification: - - Idris, Andi Muhammad Syafri (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
The aim of this study is to look into the methods teachers use to change language elements during class interactions. Reexamining how these changes are applied to improve students' understanding in light of Chaudrons' theory (1988) is the goal. A descriptive qualitative approach was chosen in order to accomplish the research goal. This approach was used to provide a thorough examination of the language adjustments instructors made when using the checklist for classroom observations and interviews as the research tool. The qualitative descriptive framework made use of the data analysis. Lexis, syntax, and phonology were the three main areas in which the three teachers who participated in the study applied linguistic adjustments, according to the findings. These modifications were purposefully made to help students understand during class interactions and to promote clearer communication. Lexical, syntactic, and phonological changes are intentional modifications to clear up possible misunderstandings and strengthen the learning process. The study suggests that useful advice that probably provides insights into how educators might successfully apply language alteration to improve the caliber of engagement in their classes.